Risk Factors for Hypertension in a Rural Dwelling - Aurangzaib , Saif ud Din Saif,Fazal Ur Rehman (Journal of Rawalpindi Medical College, 2013)
Background: To assess the frequency and common risk factors for hypertension in a rural setup. Methods: In this cross sectional study 239 people were included. A structured and pretested proforma was used to collect data regarding socio-demographic characteristics and information about different risk factors of hypertension. Information regarding blood pressure, weight and height was taken. BMI was calculated and WHO classification was used for categorization of hypertension. Results: Males constituted 49.4 %, with a male to female ratio of 1:1.02. The mean age of the participants was 46.45±5.65 years. The subjects having < 45 years of age were 59%. In this sample 55 (23%) were obese and out of 118 males, 94 (79.66%) were smokers. Patients with hypertension (including pre-hypertensive) constituted 23%. Prevalence of oral contraceptive pills among women was found in 18 %. Age was found a significant (p-value < 0.05) factor in the causation of hypertension. Males kept their predominance (p-value < 0.05) in having hypertension while smoking exhibited non significant (p-value > 0.05) association with hypertension. Obesity showed significant (p-value < 0.05) and use of contraceptive pills showed non-significant (p-value > 0.05) association with hypertension. Conclusion: The prevalence of hypertension in this study was found to be 23%. This prevalence was significantly higher in older age subjects, male participants, obese subjects and in women who were not using contraceptive pills.